HUBUNGAN BEBAN KERJA DAN KEPUASAN KERJA DENGAN INTENSI BERHENTI BEKERJA KARYAWAN CONTACT CENTER GARUDA INDONESIA - Rosadi, Gina Awalia Zulfa (2014)
The intention of employee to resign from they company is influenced by several factors such as job satisfaction and workload of employees. The Purpose of the research are: 1) knowing the general overview of workload, job satisfaction, and turnover intension; 2) knowing the correlation between workload with turnover intention; 3) knowing the correlation between job satisfaction with turnover intention; and 4) knowing the correlation between workload and job satisfaction with turnover intention. The Instrument which is applied in this research is questioner based on NASA-TLX's theory for workload, Robbins's theory for job satisfaction, and Mobley's theory for turnover intention. Sampling method which is used is sample random sampling method. Data non parametric is a result from this research which has been gained, so the correlation test used spearman-rho correlation test. The result of this research presents the workload, the job satisfaction, and the turnover intension of Garuda's Indonesia contact center in average categories. The correlation between workload and turnover intention has coefficient correlation about 0.204 and correlation of job satisfaction and turnover intention has coefficient correlation about -0.550. the workload has contribution about 4.16% and the job satisfaction has contribution about 30.25% towards turnover intention, and then, as a result the significant value in each variable is about 0.022 and 0.00 which is present the correlation of both variable are being valid for whole population